2004
DOI: 10.1158/0008-5472.can-04-1070
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Prostacyclin Synthase Overexpression Chemoprevents Tobacco Smoke Lung Carcinogenesis in Mice

Abstract: Increased pulmonary production of prostaglandin I 2 (prostacyclin) by lung-specific overexpression of prostacyclin synthase decreases lung tumor incidence and multiplicity in chemically induced murine lung cancer models. We hypothesized that pulmonary prostacyclin synthase overexpression would prevent lung carcinogenesis in tobacco-smoke exposed mice. Murine exposure to tobacco smoke is an established model of inducing pulmonary adenocarcinomas and allows for the testing of potential chemopreventive strategies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
98
2
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(108 citation statements)
references
References 43 publications
(57 reference statements)
6
98
2
2
Order By: Relevance
“…These results suggest that PPARd-dependent growth control depends on a cytostatic effect based on G1 arrest but not a cytotoxic effect. It has been reported that the induction of COX-2 and subsequent overproduction of PGs except PGI 2 contribute to the appearance of malignant phenotypes in lung adenocarcinoma cells [6,14]. From these reports, it can be assumed that the overproduction of PGs by COX except PGI 2 attenuates the PPARd-dependent negative growth control of A549 cells, so we examined the effect of L-165041 treatment on the growth of A549 cells under COX inhibition by indomethacin.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…These results suggest that PPARd-dependent growth control depends on a cytostatic effect based on G1 arrest but not a cytotoxic effect. It has been reported that the induction of COX-2 and subsequent overproduction of PGs except PGI 2 contribute to the appearance of malignant phenotypes in lung adenocarcinoma cells [6,14]. From these reports, it can be assumed that the overproduction of PGs by COX except PGI 2 attenuates the PPARd-dependent negative growth control of A549 cells, so we examined the effect of L-165041 treatment on the growth of A549 cells under COX inhibition by indomethacin.…”
Section: Resultsmentioning
confidence: 98%
“…From these reports, it is speculated that, in addition to the induction of COX-2, the suppression of PGI 2 production contributes to the development of lung adenocarcinoma. The downregulation of PGI 2 synthase is observed in lung adenocarcinoma tissue, and the expression of PGI 2 synthase in lungs leads to the reduced development of lung adenocarcinoma in mice [13,14]. However, it remains unclear which signaling pathway regulated by PGI 2 contributes to the reduction of lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…It has been known that PGD 2 and PGI 2 are anticarcinogenic agents (Keith et al, 2004;Park et al, 2007;Cathcart et al, 2010). PGD 2 is rapidly metabolized to 15-deoxy-D 12,14 -PGJ 2 , which inhibits tumor growth via a peroxisome proliferator-activated receptor g (PPARg)-dependent or -independent pathway (Scher and Pillinger, 2005;Mansure et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…It is thus conceivable that the elevated PGD 2 may be functionally linked to the increased PPARg and the decreased NF-kB in tumor tissues of mPGES-1 KO mice. It was also shown that pulmonary PGI synthase overexpression suppressed tobacco smoke-induced lung carcinogenesis in mice (Keith et al, 2004), indicating that PGI 2 , as well as PGD 2 , can be regarded as an anti-carcinogenic PG. As shown in Figure 2, ablation of mPGES-1 resulted not only in the suppression of carcinogenic PGE 2 production, mPGES-1 promotes colon carcinogenesis Y Sasaki et al but also in the reciprocal upregulation of anti-carcinogenic PGD 2 /PGI 2 production.…”
Section: Mpges-1 Promotes Colon Carcinogenesismentioning
confidence: 98%
“…Different investigations have highlighted the importance of the PTGIS expression in preventing tumor growth and progression (Keith et al, 2002;Pradono et al, 2002;Cutler et al, 2003;Keith et al, 2004). It has been suggested that some of the protective effects of PTGIS overexpression may be attributable to apoptosis activation mediated by PPARd (Hatae et al, 2001).…”
Section: Discussionmentioning
confidence: 99%